Complications of anti-TNF therapies. Issue 6 (December 2007) - Ding, Tina; Deighton, Chris
Anti-TNF drugs have revolutionized the treatment of rheumatoid arthritis (RA). Concerns about risks of infection and malignancy with these agents have led to scrutiny of available data. Patients with severe, active RA are more prone to infection and lymphoma than the general population, which confounds data interpretation. For both infection and cancer risk the data are contradictory, but suggest a) an increased risk of serious infection (∼∼ twofold), b) that vigilance is required for tuberculosis and other granulomatous and intracellular infection when screening patients, as well as close monitoring thereafter, c) no overall increased cancer risk, but concerns regarding skin cancers, and possible greater risks for patients with prior tumors. Although the advantages of these drugs far outweigh their disadvantages, we cannot be complacent about monitoring patients on anti-TNF closely. Regular updates of analyses of observational databases for emerging problems are needed.